Growth and structural change in the Egyptian economy - Mead, Donald C. (Homewood, Ill. : R. D. Irwin, 1967)
This study is concerned with an understanding not of how the Egyptian industrial sector has changed or whether there is unemployment in agriculture, but looks at how the economy as a whole operates, what dynamic forces for development are and how they spread through every corner of the economy.
Includes bibliographical references: p. 403-411.
lje 24/01/2018
Loans
Keywords: Industrialization; Economic development; Egypt